SUBCUTANEOUS FAT NECROSIS OF THE NEWBORN AND TREATMENT OF SEVERE HYPERCALCEMIA WITH LOW DOSE OF IV PAMIDRONATE: A CASE REPORT - Krishnasamy, Raiwathy; Lian, Angelie Wang Seng; Selveindran, Nalini (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Subcutaneous fat necrosis of the newborn (SCFN) is an uncommon entity that occurs in neonates who experience perinatal stress. Current treatment of patients with SCFN-related hypercalcemia includes hydration, furosemide, glucocorticoids, and diets low in calcium and vitamin D. We report the use of pamidronate, a bisphosphonate, to control hypercalcemia in a 5-week-old infant with SCFN. METHODOLOGY A term neonate was born via EMLSCS due to nonreassuring fetal status. Antenatally mother had gestational diabetes mellitus, group B streptococcus carrier and antenatal scan at 29 weeks detected fetus with dilated small bowel. Baby was born vigorous but complicated with bowel perforation requiring fluid resuscitation and a bedside glove drain. He underwent laparotomy for small bowel perforation secondary to ileal atresia and was started on TPN postoperatively while his feeding was established. At his 3rd week, he had palpable purplish lumps at his trunk and limbs associated with severe hypercalcemia and hypertriglyceridemia supporting the diagnosis of subcutaneous fat necrosis. His hypercalcemia was resistant to treatment with initial hyperhydration and IV furosemide. Further investigations showed appropriately suppressed PTH level with deficient Vitamin D levels. There was no calcification in the heart or cranium but there were pelvic, medullary and bladder calculi. RESULTS He was treated with low dose IV Pamidronate (0.2 mg/kg/dose). Post single dose of IV Pamidronate calcium levels were reduced to 2.2-3 mmol/L and furosemide was discontinued. On discharge, he tolerated low calcium formula milk. During his first follow up the calcium level remained stable at 2.5 mmol/L and repeated ultrasound showed resolution of the renal pelvis and bladder calculi with persistence of the medullary nephrocalcinosis. CONCLUSION SCFN has a potentially life-threatening complication due to development of severe hypercalcemia. Pamidronate is a safe treatment option that does not need prolonged therapy.